Exploring experiences of loneliness among Canadian long‐term care residents during the COVID‐19 pandemic: A qualitative study. (8th November 2022) - Smith, Chelsea B.; Wong, Karen Lok Yi; To‐Miles, Flora; Dunn, Sheila; Gregorio, Mario; Wong, Lily; Tam, Samantha; Huynh, Polly; Hung, Lillian
Abstract: Background: The COVID‐19 pandemic has significant impact on long‐term care (LTC) residents' health and well‐being. Objectives: This study investigated resident experiences of loneliness during the COVID‐19 pandemic in Canadian LTC homes to offer lessons learned and implications. Methods: 15 residents and 16 staff members were recruited from two large urban Canadian LTC homes with large outbreaks and fatalities. We used a telepresence robot to conduct one‐on‐one semi‐structured interviews with participants remotely. We applied the Collaborative Action Research (CAR) methodology and report the early phase of CAR focused on collecting data and reporting findings to inform actions for change. Thematic analysis was performed to identify themes. Results: Four themes were identified. The first two themes characterise what commonly generated feelings of loneliness amongst residents, including (1) social isolation and missing their family and friends and (2) feeling hopeless and grieving for lives lost. The second two themes describe what helped residents alleviate loneliness, including (3) social support and (4) creating opportunities for recreation and promoting positivity. Conclusions: Residents living in LTC experienced significant social isolation and grief during the pandemic that resulted in loneliness and other negative health consequences. Implications for practice: Promoting meaningful connection, safe recreational activities and a positive atmosphere in LTC homes during the pandemic may help mitigate residents' experiences of loneliness due to social isolation and/or grief and enhance their quality of life.